Reduction of the Relative Intensity Noise of Broadband Sources Using Dual Fiber Ring Resonator - Yishi Liu; Jingjing Su; Xiaowan Luo; Xingfan Chen (IEEE Photonics Journal, 2023)
Interferometric fiber-optic gyroscopes (IFOGs) are widely utilized due to their compact size and solid-state design. However, their sensitivity of detecting rotation is limited by the relative intensity noise (RIN) associated with the broadband source. To overcome this limitation, a conventional fiber ring resonator (FRR) can be employed to filter the RIN specifically at the IFOG frequency. Nonetheless, implementing this solution necessitates a fiber delay line with a length equal to that of the fiber coil. To address this challenge, we propose the utilization of passive and active dual FRRs and examine their RIN suppression characteristics. By utilizing the active dual FRR as an optimized gain point filter, we achieve a theoretical RIN suppression ratio equivalent to that of the traditional FRR, while significantly reducing the required length of the fiber delay line.